Miskonsepsi Dan Kesulitan Peserta Didik Sekolah Menengah Pada Materi Pertidaksamaan Kuadrat - Mirza, Ade; Wardahnia; Hamdani, Hamdani; Pasaribu, Revi Lestari (Jurnal Padegogik, 2024)
This study aims to reveal the misconceptions and difficulties of high school students in determining the set of solutions for a quadratic inequality. This research is a qualitative research in the form of a case study. The subjects of this study were six students in class X IPA 5 SMA Negeri 3 Pontianak. Data collection used test techniques (paper and pencil) with tools in the form of diagnostic tests in the form of descriptions and direct communication techniques with tools in the form of interview guides. The data that has been obtained from the results of tests and interviews is then described by categorizing it according to the indicators that have been compiled, then presented in tabular form and given a conclusion. The misconceptions found are generalizing equations to become inequalities and misinterpreting that the solution to an inequality cannot be a single solution. Meanwhile the difficulties found are (1) difficulty understanding the semantic and symbolic meaning of inequalities (2) difficulty using arithmetic skills (3) difficulty understanding the signs of the product factor (4) difficulty applying inequality rules (5) limited understanding of the number system (6) do not understand the question